A needs analysis of HOTS-based assessment instruments for elementary school mathematics learning - Yossy Melawati; Rochmiyati Rochmiyati; Nurhanurawati Nurhanurawati (Asian Journal of Educational Technology, 2022)
This study aimed to analyze an assessment needs based on Higher Order Thinking Skills (HOTS) in mathematics subjects of the fifth-grade elementary school. Analysis needs are required to find out the conditions needed in learning to achieve an educational goal. This research was conducted in a qualitative descriptive manner, with the research subject being the educators who taught the fifth grade of elementary school, with 4 educators. Research data was obtained through a questionnaire. The data analysis technique used is Miles and Huberman which consists of data reduction (data reduction), data display (data presentation), and conclusion (concluding). The result showed that it is necessary to develop Higher Order Thinking Skills (HOTS)-based mathematical assessment instrument to assist educators in making assessments, become a reference for educators to design or make HOTS-based assessments and help improve students' mathematical critical thinking skills.